Manipulating task constraints to reduce the herding behaviour in team games - Koh, Sherlyn Xiao Tian. (2013)
Young soccer players are notorious for swarming around the ball. Yet, finding space is known to be one of the essential elements to successful soccer. Task constraints have shown to be able to alter behaviour. The purpose of the study is, therefore, to put these together and establish if the manipulation of task constraints can reduce the herding behaviour that so often plagued the games of children.